Trichoderma strains with endophytic capacity on the control of the mildew (Peronospora variabilis Gäum) and improve quinoa yield - Leon Ttacca, Betsabe (2018)
Downy mildew is the most important disease that affects quinoa (Chenopodium quinoa Willd.) in the Peruvian altiplano, it’s caused by pseudo fungi Peronospora variabilis Gäum. It causes yield reductions up to 99%. With the purpose of evaluating the effect of Trichoderma sp strains with endophytic capacity in the control of the mildew and improve quinoa yield var. Salcedo INIA, the seeds were fully covered (1x106 ufc. seed-1) and substrate was infested with spores of 10 Trichoderma strains to determine the percentage of endophytic colonization in quinoa plants at 30 and 60 days age under controlled conditions;four leaf applications (1x107 ufc.ml-1) and severity evaluations were also performed to determine the area under the disease progress curve (AUDPC) and grain yield under field conditions. All the strains managed to colonize different parts of the plant confirming to be endophytes of quinoa. The highest percentage of infestation (34.24 %) was achieved inoculating the substrate with the strain T10 which level of colonization reached 60%, followed by T3 with 56.67% and T2 with 43.33%. The scoring after 60 days showed that plants treated with strains T1, T3 and T2 were the least affected by downy mildew with values of 615.7, 706.8 and 759 for AUDPC, respectively. They also displayed the highest values for grain yield 3127.30, 3029.12 and 2866.57 kg. ha-1, respectively, in comparison with the control which AUDPC and yield were 1670.5 and 1141.27 kg. ha-1